Plasmon standing waves by oxidation of Si(553)–Au - Mamiyev, Zamin; Tzschoppe, Michael; Huck, Christian; Pucci, Annemarie (The journal of physical chemistry. C, Energy, materials, and catalysis, 2019)
Self-assembled Au atomic wires on stepped Si surfaces are metallic, as evidenced by one-dimensionally dispersing plasmonic excitation. Here, we investigate the effects of oxidation on metallicity along such Au atomic wires on a regularly stepped Si(553) surface by employing infrared absorption and high-resolution electron energy loss spectroscopies. Our results indicate that only the Si environment undergoes oxidation, which has a remarkably small effect on the plasmon dispersion. However, close to k∥ → 0 the plasmon dispersion starts at increasingly higher energies as a function of oxygen exposure, which is attributed to standing wave formation on small sections of Au wires generated by the introduction of O atoms as scattering centers, not to electronic gap opening. This interpretation is in full agreement with the findings by infrared spectroscopy and low-energy electron diffraction.